PHYTOCHEMICAL CONSTITUENT, ACUTE AND SUBACUTE TOXICITY STUDIES OF METHANOL EXTRACT OF LAPORTEA AESTUANS LEAF - Adeosun, Abiola; Akamo, A. J.; Akinloye, O. A.; Shotuyo, A. L. A. (FUDMA JOURNAL OF SCIENCES, 2022)
Laportea aestuans is an African herbaceous weed. This work assessed the bioactive compound content of methanol extract of Laportea aestuans leaf (LALME) and its acute and subacute toxicity effects in Male Wistar rats. According to qualitative and quantitative phytochemical analysis, LALME possesses a significant amount of phenolics, flavonoids, alkaloids, tannin, carotenoids, and anthraquinones. LALME is regarded as safe because it did not cause death in rats when given doses of up to 2,000 mg/kg body weight. LALME at 200 and 400 mg/kg markedly increased (p<0.05) serum activity of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and gamma-glutamyl transferase (GGT). There was a decrease in liver LDH activity in rats administered LALME, but no significant alteration was noticed in the serum of the rats. The total bilirubin concentration in the serum of rats given 200 mg/kg LALME and in the liver of rats administered 200 and 400 mg/kg LALME was significantly higher (p<0.05) than that in the serum and liver of control rats. The serum of rats given LALME had a nearly threefold increase in direct bilirubin compared to control. However, rats administered 200 mg/kg of LALME had an increased serum urea concentration compared to control. When comparing photomicrographs of the liver and kidney of rats given LALME to those of control rats, the liver and kidney of rats given LALME showed minor congestion and renal dissemination, respectively. In conclusion, LALME was found to be safe in acute toxicity; nevertheless, subacute administration may cause variations in